Mesenchymal stem cell therapy in amyotrophic lateral sclerosis (ALS) patients: A comprehensive review of disease information and future perspectives - Shahrzad Najafi; Parizad Najafi; Najmeh Kaffash Farkhad; Ghazal Hosseini Torshizi; Reza Assaran Darban; Amir Reza Boroumand; Sajad Sahab-Negah; Mohammad Ali Khodadoust; Jalil Tavakol Afshari (Iranian Journal of Basic Medical Sciences, 2023)
Amyotrophic lateral sclerosis (ALS) is a rare deadly progressive neurological disease that primarily affects the upper and lower motor neurons with an annual incidence rate of 0.6 to 3.8 per 100,000 people. Weakening and gradual atrophy of the voluntary muscles are the first signs of the disease onset affecting all aspects of patients’ lives, including eating, speaking, moving, and even breathing. Only 5-10% of patients have a familial type of the disease and show an autosomal dominant pattern, but the cause of the disease is unknown in the remaining 90% of patients (Sporadic ALS). However, in both types of disease, the patient’s survival is 2 to 5 years from the disease onset. Some clinical and molecular biomarkers, Magnetic Resonance Imaging (MRI), blood or urine test, muscle biopsy, and genetic testing are complementary methods for disease diagnosis. Unfortunately, with the exception of Riluzole, the only medically approved drug for the management of this disease, there is still no definitive cure for it. In this regard, the use of Mesenchymal Stem Cells (MSCs) for the treatment or management of the disease has been common in preclinical and clinical studies for many years. MSCs are multipotent cells having immunoregulatory, anti-inflammatory, and differentiation ability that makes them a good candidate for this purpose. This review article aims to discuss multiple aspects of ALS disease and focus on MSCs’ role in disease management based on performed clinical trials.